Экономичный когерентный приемопередатчик Ка-диапазона для мобильных РЛС ближнего радиуса действия - Khitrovsky, V. A.; Berkuta, D. N. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The results of the development of an economical Ka-band coherent transceiver with continuous phase-coded signal emission for patrol radars are presented. The receiver sensitivity in the video frequency band of 0–6 MHz was not less than –125 dB·W, and the dynamic range was at least 60 dB. The secondary power supply unit operates from a primary voltage of +12 V supplied by a battery.